Federalisasi dan Demokratisasi Indonesia - Samsu Rizal Panggabean (Jurnal Ilmu Sosial dan Ilmu Politik, 1998)
This article, the first of two articles, maintains that federalism is a democratic solution to problems of governance in contemporary Indonesia, despite its present abuse as a term. Four reasons are introduced as to why "federalization" should be included in the process of democratization in Indonesia. Theyare: (I) federalism unveils power; (2)respcects social and political pluralism, (3) facilitates a just and participatory development, and (4) avoids disintegration.